Mindset According to the Qur'an: A Study of Tahlili in Surah Al-Fatihah Verse 7 - Ilmi, Fadilatul; Kuswoyo, Nyoko Adi; Rohtih, Wiwin Ainis; Mahmud, Amir (Literacy: Journal of Education and Social Science, 2024)
Surah al-Fatihah is known by various other names. First, Surah al-fatihah, this surah is the opening surah of the Qur'an and is read in every prayer, as explained by Ath-Thabari. Second, Ummul Kitab, which means "Mother of the Book," this surah covers the essence of the teachings of the Qur'an. In this surah al-fatihah, there is also praise to Allah, recognition of His power, devotion to Him, obedience to His commands and prohibitions, and a request to be guided to His pleasure. The name "um" in Arabic is often used to refer to something that encompasses a variety of things. During life, whether consciously or unconsciously, the mind has a great influence in dealing with all situations, and can even affect changes in a person. The outward appearance of a human being is a reflection of his inner world. A person becomes what he thinks, because the mind gives energy to realize what he wants to achieve. The prophets chosen by God to get guidance and guide mankind to the truth, have a special way of thinking. They always say and act correctly, have seriousness, trust, intelligence, and openness, and convey something that must be conveyed. They are awakened from sin and transgression, keeping their identity well. Likewise the story experienced by the prophet Ayyub As.